2019
DOI: 10.1021/acs.est.9b03765
|View full text |Cite|
|
Sign up to set email alerts
|

Resourcing the Fairytale Country with Wind Power: A Dynamic Material Flow Analysis

Abstract: Wind energy is key to addressing the global climate challenge, but its development is subject to potential constraints of finite primary materials. Prior studies on material demand forecasting of wind power development are often limited to a few materials and with low technological resolution, thus hindering a comprehensive understanding of the impact of microengineering parameters on the resource implications of wind energy. In this study, we developed a component-by-component and stock-driven prospective mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 46 publications
0
39
0
3
Order By: Relevance
“…Similar to other studies, 14,16 our predictions on future windpower development and its corresponding RE demand are subjective to the scenario assumptions and model uncertainty. To validate the dynamic material-flow-analysis model we used in this study, we collected and reviewed all relevant studies in Table S7 to compare results, and we found that our estimated global Nd demand is consistent with most previous studies (Figure S1).…”
Section: Discussion Model Validation and Sensitivity Analysismentioning
confidence: 77%
See 1 more Smart Citation
“…Similar to other studies, 14,16 our predictions on future windpower development and its corresponding RE demand are subjective to the scenario assumptions and model uncertainty. To validate the dynamic material-flow-analysis model we used in this study, we collected and reviewed all relevant studies in Table S7 to compare results, and we found that our estimated global Nd demand is consistent with most previous studies (Figure S1).…”
Section: Discussion Model Validation and Sensitivity Analysismentioning
confidence: 77%
“…9 Those REs are critical to the efficiency and market competitiveness of wind turbines, 10 but they are relatively scarce and experiencing a vulnerable global supply chain when the whole world is relying on the production from only a few countries. 11,12 Several initial investigations have attempted to address such conflicts to meet wind-powerdevelopment targets in several countries, such as China, 13 the United States, 14,15 Denmark, 16 and Germany, 17 which all urge to incorporate RE constraint into the design of a wind-power roadmap. For instance, Fishman and Graedel found that there will be a shortage of Nd for the delivery of United States offshore wind-power targets even if the REs in retired turbines are well recycled.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical regressions of engineering parameters of the wind turbines including the material composition specifications, capacities, decommissioned capacities, sizes, scaling effects, and materials flows were adapted from the previous works of Cao et al [42]. Information was extracted from several databases such as the UKWED [25]; The Wind Power [26]; Wind Power Offshore [43]; 4C Offshore, 2018 [19] and combined with literature surveys internet were used to develop a novel database.…”
Section: Methodology and Data Analyticsmentioning
confidence: 99%
“…Jacket foundations are the second most prevalent having been installed at 4 of the 37 sites, while gravity-based and floating spar foundations are only installed at one site each. All are made almost entirely from steel, except gravitybased foundations which contain both steel and concrete [42,[44][45][46] Monopile Kiełkiewicz et al [47], demonstrated a pattern between monopile foundation weight and sea depth for 3.3 MW and 8 MW turbines. These patterns have been applied to the relevant offshore wind farms within this study to estimate monopile foundation weights.…”
Section: Foundationsmentioning
confidence: 99%
“…In addition, there are several growing trends in terms of energy generation technologies and the transition to clean energy. Stock levels, materials requirements, and materials efficiencies are all factors to consider [98][99][100][101]. Other studies were more concerned with natural disasters: earthquakes, tsunamis, and floods.…”
Section: Industrial Ecology and Urban Metabolismmentioning
confidence: 99%